The Strategic Christian Institution: Applying Strategic Management Theory to Lay Evangelization Organizations - Simon, Victor Joel Feria (2005)
Every organization requires a clear direction, a plan, a strategy. This dissertation is focussed on the process of planning and strategizing in Christian lay-evangelization institutions. It states broad guidelines for an overall approach to an effective strategic planning process for any evangelization institution. An "overall approach" involves taking into account the whole situation of these institutions and trying to understand what should be done in order to advance towards the vision of the institution.